Evaluation of at-home serum anti-Müllerian hormone testing: a head-to-head comparison study - Erin Silliman; Esther H. Chung; Elizabeth Fitzpatrick; Julie A. Jolin; Michelle Brown; James Hotaling; Aaron K. Styer; Anatte E. Karmon (Reproductive Biology and Endocrinology, 2022)
Abstract Background For optimal fertility testing, serum anti-Müllerian hormone levels are used in combination with other testing to provide reliable ovarian reserve evaluations. The use of the ADx 100 card is widely commercially available for at-home reproductive hormone testing, but data demonstrating that its results are reproducible outside of a clinical setting are limited, as well as comparisons of its performance with other newer blood collection techniques. This study aimed to evaluate the concordance of serum AMH levels found via standard venipuncture and self-administered blood collection using the TAP II device (TAP) and ADx card in women of reproductive age. Methods This was a prospective, head-to-head-to-head within-person crossover comparison trial that included 41 women of reproductive age (20–39 years). It was hypothesized that the TAP device would be superior to the ADx card both in terms of agreement with venipuncture reference standard and patient experience. Each subject had their blood drawn using the three modalities (TAP, ADx, and venipuncture). We evaluated the concordance of AMH assays from samples obtained via the TAP device and ADx card with the gold standard being venipuncture. Two-sided 95% CIs were generated for each method to compare relative performance across all three modes. Patient preference for the TAP device versus the ADx card was based on self-reported pain and Net Promoter Score (NPS). Results The TAP device was superior to the ADx card on all outcome measures. TAP R-squared with venipuncture was 0.99 (95% CI 0.99, > 0.99), significantly higher than the ADx card, which had an R-squared of 0.87 (95% CI 0.80, 0.94) under most favorable treatment. TAP sensitivity and specificity were both 100% (no clinical disagreement with venipuncture), versus 100 and 88%, respectively, for the ADx card. Average pain reported by users of the TAP device was significantly lower than the ADx card (0.75 versus 2.73, p < 0.01) and the NPS was significantly higher than the ADx card (+ 72 versus − 48, p < 0.01). Conclusions The TAP was non-inferior to venipuncture and superior to the ADx card with respect to correlation and false positives. Moreover, the TAP was superior to both alternatives on patient experience. Trial registration NCT04784325 (Mar 5, 2021).